Improving access to and use of maternal health services during COVID-19: Experience from a health system strengthening project in Guinea - Kouyate, Mariama; Barry, Lansana; Sow, Abdoulaye; De Maesschalck, John; De Put, Willem Van; Sidibé, Sidikiba; Adrianaivo, Norohaingo; Kolié, Delphin; Delamou, Alexandre (Frontiers in Public Health, 2022)
The purpose of this study was to document the experience of capacity strengthening for health providers and its contribution to the resilience of the health system and the population in the Republic of Guinea. It was a cross-sectional study using routine data from 2019 to 2021 from the 41 health facilities in the intervention areas. The quantitative results showed that all the CMCs had a clean internal and external environment, compared to 95.2% of the community health centers (AHCs) and health centers and 33.3% of the hospitals. Hand washing of visitors was routine in CMCs and HPs. However, 28.6% of visitors in the AHCs did not wash their hands. Temperature taking for visitors was not performed in all CMCs and in 90.5% of the AHCs; unlike in the HC and HP where the temperature of each patient was taken before entering the consultation room. The obligation to wear masks was higher in the HP and in the HC, contrary to the CMC and AHC where the order of non-compliance with the wearing of masks was respectively 36.4% and 19%. Non-compliance with social distancing in the waiting rooms and between users was observed in all facilities. The project's interventions mainly improved the use of prenatal consultation and institutional delivery services; the beginning of the interventions was marked by an increase of an average of 17 ANC1 per month in the CMCs and 116 ANC1 in the health centers. Ongoing training on capacity strengthening for providers in infection prevention and control, followed by the offering of delivery kits and materials during epidemics, would contribute to the improvement and use of health facilities by the population.